Perfil emprendedor y empoderamiento femenino. Casos de estudio: Asociación Grano de Oro y Unión y Progreso, cantón Latacunga. - Carrera Bracho, Lidia Rosaura (2020)
This research aimed to analyze the level of empowerment and the entrepreneurial profile of Grano de Oro and Unión y Progreso associations. Two instruments were applied in this research, one on empowerment proposed by Hernández and García (2008), and another on the entrepreneurial profile by Flores (2003), sociodemographic variables were incorporated that allowed to complete the analysis. The results show different levels of empowerment, high for the Unión y Progreso Association, and medium for the Grano de Oro Association, as well as in the entrepreneurial profile, which is higher in the first case. Furthermore, empirical evidence shows that the relationship between empowerment and entrepreneurial profile is low. Based on these results, a training proposal was generated to strengthen female empowerment and provide management skills to women in order to consolidate their economic initiatives.